ANALISIS PENGARUH MODAL USAHA, LAMA USAHA DAN TENAGA KERJA TERHADAP PENDAPATAN USAHA BENGKEL MOTOR DI DESA JENGGIK - Lalu Muh Irpan Alawi; Sahar Sahar; Bq Rizka Milania Ulfah (Fakultas Ekonomi Universitas Islam Al-Azhar, 2022)
The purposes of this study are 1) To find out whether business capital has an effect on the income of a motorcycle repair shop in Jenggik village. 2) To find out whether the length of the business has an effect on the income of the motorcycle repair shop in Jenggik village. 3) To find out whether the labor has an effect on the income of the motorcycle repair shop in Jenggik village. 4) To find out whether capital, length of business, and labor have a simultaneous effect on the income of a motorcycle repair shop in Jenggik village. The research method used is associative with a quantitative approach. This research was conducted in Jenggik Village, Terara - East Lombok. The sample in this study were 12 motorcycle repair shop entrepreneurs in Jnggik Village. The data collection technique used in this study was a questionnaire. The data analysis tool uses multiple linear regression analysis, T test, F test, and the coefficient of determination test (R2). The results of this study indicate that: 1) Business capital has a significant partial effect on the income of a motorcycle repair shop in Jenggik Village. 2) The length of business has a significant partial effect on the income of the motorcycle repair shop in Jenggik Village. 3) Labor does not partially affect the income of the motorcycle repair shop in Jenggik Village. 4) Business capital, length of business and labor simultaneously or together have an effect on the income of the motorcycle repair business in Jenggik Village.